A Hydronium Solvate Ionic Liquid: Ligand Exchange Conduction Driven by Labile Solvation. Issue 9 (13th June 2018) - Kitada, Atsushi; Kintsu, Kohei; Takeoka, Shun; Fukami, Kazuhiro; Saimura, Masayuki; Nagata, Takashi; Katahira, Masato; Murase, Kuniaki
Abstract : We observed a new class of proton conduction in a hydronium (H3 O + ) solvate ionic liquid (IL). The IL is described as [H3 O + ·18C6]Tf2 N, composed of 18-crown-6-ether (18C6)-coordinated H3 O + cation (solvate) and bis(trifluoromethylsulfonyl)amide (Tf2 N − ; Tf = CF3 SO2 ) anion. Self-diffusion coefficient measurements revealed that protons of H3 O + (solute ion) move faster than 18C6 ligand (solvent), marking the first observation of ligand exchange conduction not only among solvate ILs but also among protic ILs without free neutral molecules. The presence of ligand exchange conduction without inducing external electric field indicates that solvation of H3 O + by 18C6 is kinetically labile, i.e. ligand exchange is very fast for the reaction H2 O + 18C6 + HTf2 N ⇌ [H3 O + ·18C6]Tf2 N, while the equilibrium shifts to the right. The fundamental findings regarding the hydronium solvate IL will help in the design of proton conductors.